Parodia política y oración: glosas mexicanas al Padrenuestro (de la Colonia a nuestros días) - Ana Castaño (Prof. Dr. Vittoria Borsò, Prof. Dr. Frank Leinen, Jun.-Prof. Dr. Yasmin Temelli, Prof. Dr. Guido Rings, 2013)
The Lord’s Prayer is a long-established literary theme in European literature. Its literary manifestations range from the almost literal devotional paraphrase to the burlesque and subversive recreation; and from the cultured expressions, heirs of the rich exegetical tradition around this prayer, to those of a more popular vein, derived from an equally rich oral tradition. In my article I refer to a selection of glossed Lord’s Prayers, of popular vein, which belong to a curious line of "political" Lord’s Prayers, that is, addressed to rulers or to certain groups of power and which generally are an expression of protest, criticism or satire towards these groups and institutions. They were composed in colonial Mexico and, later, in independent Mexico. All of them come from popular manuscripts or printed material, were in Mexican archives and collections and appear here for the first time – except for one of them – in a modern publication, accompanied by some notes and contextual explanations. They have in common the popular tone, being put in the mouth of the Mexican people and a decidedly critical attitude – with more or less parodic content – against the presence of the Spanish in Mexico.